The Influence Of Information And Communication Technology (ICT) Development On Income Inequality Through Economic Development - Sandra Olivia Pratiwi; Muhammad Hanri (UNIVED Press, 2024)
Over the last few decades, the development of information and communication technology (ICT) has had a major impact on the economy and society more broadly. There is currently a consensus that developments in information and communication technology (ICT) can provide a boost to sustainable economic development. This study aims to analyze the influence of the development of information and communication technology (ICT) on income inequality through economic development in Indonesia. Analysis of the research uses econometric analysis using the fixed effect model with the Two-Stage-Least-Square (TSLS) method with a period of 2017–2021 to understand the extent to which the development of information and communication technology (ICT) can facilitate reducing income inequality through economic development. The data used in this study came from the Central Statistics Agency (BPS), the Ministry of Finance of the Republic of Indonesia, the Ministry of Communication and Information, and the National Socioeconomic Survey (SUSENAS). The results of this study found that the influence of significant positive ICT development can encourage reduced income inequality through economic development in Indonesia. Social assistance provided by the government has shown significant help in reducing inequality in Indonesia. ICT development can encourage reducing inequality and economic development outside Java Island but not in Java Island. The influence of ICT development is greater in provinces with the lowest service sector compared to provinces with the highest service sector.